Sky-blue nondoped OLEDs based on new AIEgens: ultrahigh brightness, remarkable efficiency and low efficiency roll-off. (29th September 2016) - Chen, Long; Lin, Gengwei; Peng, Huiren; Ding, Siyang; Luo, Wenwen; Hu, Rongrong; Chen, Shuming; Huang, Fei; Qin, Anjun; Zhao, Zujin; Tang, Ben Zhong
Abstract : Nondoped OLEDs based on a 4-(dimesitylboryl)fluorenyl functionalized TPE derivative show sky-blue electroluminescence, remarkable efficiencies, ultrahigh brightness and low efficiency roll-off. Abstract : Two novel AIEgens decorated with fluorenyl and dimesitylboryl groups are prepared. They show high thermal stability and excellent solid-state photoluminescence efficiency. Sky-blue nondoped OLEDs are achieved based on them, affording remarkable electroluminescence efficiencies (12.2 cd A −1 and 5.3%), ultrahigh brightness (92 810 cd m −2 ) and low efficiency roll-off (11.0 cd A −1 at 1000 cd m −2 ).